2019
DOI: 10.1002/cam4.2622
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding small nucleolar RNA host genes in digestive cancers

Abstract: Although long noncoding RNAs (lncRNAs) do not have protein coding capacities, they are involved in the pathogenesis of many types of cancers, including hepatocellular carcinoma, cervical cancer, and gastric cancer. Notably, the roles of lncRNAs are vital in nearly every aspect of tumor biology. Long non‐coding small nucleolar RNA host genes (lnc‐SNHGs) are abnormally expressed in multiple cancers, including urologic neoplasms, respiratory tumors, and digestive cancers, and play vital roles in these cancers. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 112 publications
(283 reference statements)
1
56
0
Order By: Relevance
“…Dysregulation of the lncRNAs in bronchial epitheliums may contribute to the field cancerization in lung carcinogenesis. The SNHG family includes numerous members, whose dysregulations are associated with a variety of malignancies [53]. Each SNHG might contribute to tumorigenesis via multiple molecular regulatory mechanisms [53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysregulation of the lncRNAs in bronchial epitheliums may contribute to the field cancerization in lung carcinogenesis. The SNHG family includes numerous members, whose dysregulations are associated with a variety of malignancies [53]. Each SNHG might contribute to tumorigenesis via multiple molecular regulatory mechanisms [53].…”
Section: Discussionmentioning
confidence: 99%
“…The SNHG family includes numerous members, whose dysregulations are associated with a variety of malignancies [53]. Each SNHG might contribute to tumorigenesis via multiple molecular regulatory mechanisms [53]. For example, some SNHGs could act as sponges of microRNAs to inhibit the roles of miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Small nucleolar RNA host gene 12 (SNHG12) is one of the classes of SNHGs [7]. Studies revealed that SNHG12 regulate cell proliferation, migration, invasion and metastasis in several cancers [8][9][10][11][12], indicating a potential target for cancer-directed interventions [13].…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidences suggested that long non-coding RNAs (LncRNAs) controls tumorigenesis and development through regulating expressions of target genes (4)(5)(6). Importantly, a number of aberrant LncRNAs have been reported to be involved in cancer chemoresistance (7,8).…”
Section: Introductionmentioning
confidence: 99%